Rekayasa Ekologi dalam Perspektif Pengelolaan Tanaman Padi Terpadu - Baehaki S. E.; Nugraha Budi Eka Irianto; Surachmad W. Widodo (Iptek Tanaman Pangan, 2016)
Ecological engineering is a form of ecological services for the agro-ecosystem restoration in order the whole control factors work naturally, toward to sustainable of life. Ecological engineering in integrated crop management (ICM) provides ecological services to empowering rice varieties, nutrition, irrigation, pest, and weed control. Integrated varieties management is a form of ecological services to improve the ecological stability of genotypes biodiversity through the assembly of resistant varieties that equipped with a functional character to be applied as a mosaic varieties. Integrated nutrition management is a form of ecological services to improve the performance of the phosphate solubilizing bacteria (PSB), potassium solubilizing bacteria (KSB), and sulfur oxidizing bacteria in an organic fertilizer as a mediator and the basic material of inorganic fertilizer as a starter. Integrated pest management is a form of ecological services through dynamics interactive between plant-pest-natural enemies based SIPALAPA, ROPALAPA, enrichment parasitoids and predators, plant traps and light traps. The use of light traps to determine the economic threshold, control strategies, and help the natural enemies when it works exceed the limits. Integrated water management to provide services in the regulation of water directly or regulation of relative humidity and temperature indirectly in providing a suitable environment for natural enemies and soil microbes. Integrated pest management uses selective insecticides to the area of target pests to serve the natural enemies that work over load.